Wireless Information and Power Transfer: Theory and Practice - Schober, Robert (Wiley-IEEE Press, 2019)
Wireless Information and Power Transfer offers an authoritative and comprehensive guide to the theory, models, techniques, implementation and application of wireless information and power transfer (WIPT) in energy-constrained wireless communication networks. With contributions from an international panel of experts, this important resource covers the various aspects of WIPT systems such as, system modeling, physical layer techniques, resource allocation and performance analysis. The contributors also explore targeted research problems typically encountered when designing WIPT systems.